Parents' perception of physical activity importance in children's Health. - Galvão, Dulce Maria Pereira Garcia (2024)
Garcia Galvão, D. M. P., Santos, C. P. & Carvalho, M. A. C. Parents' perception of physical activity importance in children's Health. Book_Pediatrics & Neonatology_ 2024. 4th World Congress on Pediatrics & Neonatology, 30 e 31 de julho de 2024, organizado por Inovine Conferences. p.42.